Dual diaphragmatic anomalies - Arjun Padmanabhan; Abin Varghese Thomas (Lung India, 2016)
Although diaphragmatic anomalies such as an eventration and hiatus hernia are commonly encountered in incidental chest X-ray imaging, the presence of concomitant multiple anomalies is extremely rare. This is all the more true in adults. Herein, we present the case of a 75-year-old female, while undergoing a routine chest X-ray imaging, was found to have eventration of right hemidiaphragm along with a hiatus hernia as well.